2003
DOI: 10.17221/4146-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage and reduced herbicide doses on weed biomass production in winter and spring cereals

Abstract: The effects of different tillage systems and dose reduction on the efficacy of triasulfuron & chlortoluron mixture in the post-emergence control of annual broad-leaved weeds in winter wheat and spring barley were studied on lessive pseudogley soil in north-eastern Croatia during 1997-2000. Total dry biomass production in untreated plots was significantly influenced by tillage and it was lowest in continuous mouldboard ploughing (99 kg/ha), medium and similar in mouldboard ploughing/disk harrowing alternating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The RT treatment did not express similar peaks, and compaction was significantly lower than CT at given depths (10-21 and 28-39 cm). In the first season (2008/09), there was a significantly higher mass of the weed at RT in comparison with CT (Table 1), whereas there were no significant differences among herbicide treatments, although results suggest that all herbicide treatments reduced weed biomass in comparison with the herbicide control (NH), which confirms finding of Knežević et al (2003) that half herbicide dosages can suppress weed as effectively as recommended dosages. Higher weed pressure on RT, however, significantly reduced winter wheat yield in comparison with CT ( Table 2), most likely due to the competition for water in a dry spring season of 2009.…”
Section: Resultssupporting
confidence: 67%
“…The RT treatment did not express similar peaks, and compaction was significantly lower than CT at given depths (10-21 and 28-39 cm). In the first season (2008/09), there was a significantly higher mass of the weed at RT in comparison with CT (Table 1), whereas there were no significant differences among herbicide treatments, although results suggest that all herbicide treatments reduced weed biomass in comparison with the herbicide control (NH), which confirms finding of Knežević et al (2003) that half herbicide dosages can suppress weed as effectively as recommended dosages. Higher weed pressure on RT, however, significantly reduced winter wheat yield in comparison with CT ( Table 2), most likely due to the competition for water in a dry spring season of 2009.…”
Section: Resultssupporting
confidence: 67%
“…Increasing the dose of herbicide application from 1.5 to 3.5 li/ha enhanced the percent of weed biomass control; weeds biomass control was nearly 100% in 3.5 li/ha. Knezevic et al (2003) reported that although the full dose of herbicide caused the highest weed control, 25% of the full dose also resulted in an acceptable weed control [18]. Red bean yield and yield components.…”
Section: Resultsmentioning
confidence: 99%
“…At the investigated locations, a typical common weed flora for the wheat community of Eastern Croatia was determined [43,44]. According to the life cycle and the leaf shape, most weed species belonged to annual broadleaf species.…”
Section: Weed Species Compositionmentioning
confidence: 99%